Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination

Suzuki cross-coupling and intramolecular aza-michael addition reaction sequence towards the synthesis of 1,10b-epi-7-deoxypancratistatins and their cytotoxicity studies - Pandey, Ganesh; Balakrishnan, Madhesan; Swaroop, Pandrangi Siva (European Journal of Organic Chemistry, 2008)
The development of an efficient approach to the construction of a phenanthridone is described. The convergent strategy commences with the preparation of Suzuki cross-coupling reaction precursors, arylboronic acid 12 and a-iodo enone 14, from piperonylamine (9) and (-)-D-quinic acid (10), respectively. The coupling of 12 and 19 followed by a key intramolecular aza-Michael addition produced phenanthridone 21 featuring a cis-fused B-C ring junction. The syntheses of compounds 25 and 26, both of which are C-1 and C-10b epimers of the naturally occurring potent antitumor agent 7-deoxypancratistatin (2), from 21 are elaborated in detail in this paper. The cytotoxicities of 25 and 26 were evaluated against three different cancer cell lines. Compound 26 served as a moderate growth inhibitor of THP-1 monocytic cells (GI(50) = 14.5 mu g/mL). ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: antitumor agents; Chiral pool; Cross-coupling; Intramolecular aza-Michael addition; Pancratistatin

Modular synthesis of biaryl-substituted phosphine ligands: application in microwave-assisted palladium-catalyzed C-N cross-coupling reactions - Singh, Chandani; Rathod, Jayant; Jha, Vishwajeet; Panossian, Armen; Kumar, Pradeep; Leroux, Frederic R. (European Journal of Organic Chemistry, 2015)
Biaryl-substituted monophosphine-based ligands have been synthesized by transition-metal-free ARYNE cross-coupling reaction of aryllithiums with 1,2-dibromobenzene and subsequent regioselective functionalization through bromine-lithium interconversion. These ligands were employed in palladium-catalyzed C-N bond-forming reactions. The reaction was found to be general with wide substrate applicability. A wide variety of both primary and secondary amines were successfully coupled with an array of differently substituted halobenzenes under microwave irradiation to give the expected products in good to excellent yields. A number of biaryl-substituted phosphine ligands screened for the coupling reaction showed that steric bulk and the electronic properties of substituents on phosphorus play a crucial role in governing the catalytic activity of C-N cross-coupling reactions.
Keywords: Biaryls; Cross-coupling; Homogeneous catalysis; Microwave chemistry; Palladium; Phosphines; synthetic methods

Efficient route to 3,3 `-biindolinylidene-diones by iron-catalyzed dimerization of isatins - Jagtap, Rahul A.; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Iron-catalyzed dimerization of various isatin derivatives is described for the efficient synthesis of 3,3 `-biindolinylidene-diones (isoindigos). The reaction provides easy access to self-coupled and cross-coupled 3,3 `-indolinylidene-diones that have high relevance to biology and materials. This Fe(0)- or Fe(II)-catalyzed dimerization reaction tolerates a wide range of functionalities, such as fluoro, chloro, bromo, alkenyl, nitrile, ether, ester, pyrrolyl, indolyl and carbazolyl groups, including cyclic and acyclic alkyls as well as an alkyl-bearing fatty-alcohol moiety. Especially, the coupling between two distinct isatins provided excellent selectivity for the cross-dimerization with trace of self-couplings. The single-crystal X-ray diffraction study established the molecular structure of eight dimerized products. A preliminary mechanistic study of the Fe-catalyzed dimerization supported the radical pathway for the reaction.
Keywords: Cross-coupling; dimerization; iron; Isatin; Isoindigo; Mechanism

Oxime ligands: organometallic synthesis and catalysis - Iyer, Suresh (SYNTHETIC COMMUNICATIONS, 2024)
Ligands are at the heart of coordination chemistry. They conjure the magic of transition metals expressed in organometallic catalysis. Phosphine or P-ligands have found vast utility in transition metal chemistry, though demanding tedious synthesis. Several N, S-based ligands also find application in organometallic chemistry. Oximes are easily derived from aldehydes and ketones by simple reactions with hydroxylamine. Thus, an extensive library of oximes is available with different structural and electronic variations essential for coordination chemistry and catalysis. Several compounds with complex structural features, unavailable for phosphorous ligands, can be readily converted into active oxime ligands in a single derivatization step. Oxime ligands and metal complexes are applied in synthesizing diverse organic molecules and thus versatile ligands in organotransition metal chemistry.
Keywords: cobaloxime; Cross-coupling; oxime palladacycles; oximes; radical cyclization